Living the gospel of Jesus Christ : Orthodox and Evangelical approaches to discipleship and Christian formation - Oxbrow, Mark (Anglican priest); Grass, Tim (Oxford, UK : Regnum Books International, 2021)
Living the Gospel of Jesus Christ addresses the challenge of whole-life discipleship and Christian formation for the contemporary church. Authors from around the world bring together insights from their Evangelical and Orthodox traditions to enrich the journey of witness and martyrdom, a faithful daily living of the Christian gospel which speaks with integrity to a world seeking truth.
Introduction / Mark Oxbrow, Tim Grass -- What is the Gospel in Eastern Orthodoxy? / Bradley Nassif -- Gospel as foundation for mission : the theological basis / Rosalee Velloso Ewell -- The good news of the Gospel / Michael J. Oleksa -- Learning from Paul together : how new insights into Paul's teaching can help move us forward in mission / N.T. Wright -- Learning from Paul together : an Orthodox response / John A. Jillions -- Discipleship between the traditions / David Lyons, Ralph Lee -- Why discipleship, or, Making disciples, matters / Joshua Bogunjoko, Ken Baker, Tom Lunsford -- Why discipleship matters : a response to Joshua Bogunjoko / James Nicholas -- Re-centering the Bible in the missional goal of theological education / Chris Wright -- Teaching the Bible : how can we do this better together? / Eric George Tosi -- Educating ecumenically : how does appreciation of a broader ecumenical context help us? / Sergey Koryakin, Vladimir Strelov -- Learning from three centuries of Orthodox-Evangelical encounter in the Middle East / Tim Grass -- Discipleship on the margins / Luke A. Veronis -- Discipleship shifts learned from the margins / Karen Wilk -- The future of African Christian theology : convergences between ancient Ethiopian Orthodoxy and contemporary Evangelicalism / Tekletsadik Belachew -- Mission and martyrdom : a reappraisal of Mark in African context / Mark Oxbrow -- St. Mark, from mission to martyrdom : a Coptic perspective / Irini Thabet -- Bibliography / Mark Oxbrow, Nathan Hoppe.
Online resource; title from digital title page (viewed on August 25, 2021).
JSTOR
Keywords: Christian life -- Orthodox Eastern authors; Christian life -- Evangelical authors; Discipling (Christianity); Spiritual formation -- Christianity; Formation de disciples (Religion); Christian life; Evangelicalism